Long-Term Colony Dynamics and Fitness in a Colonial Tent-Web Spider Cyrtophora citricola - Yip, Eric C.; Smith, Deborah R.; Lubin, Yael (Frontiers in Ecology and Evolution, 2021)
Social animals are expected to experience a positive effect of conspecific number or density on fitness (an Allee effect) because of the benefits of group living. However, social animals also often disperse to live either solitarily or in small groups, so to understand why social animals leave their groups it is necessary to understand how group size affects both average fitness and the expected fitness outcomes of individuals. We examined the relationships between group size and fitness in the colonial spider Cyrtophora citricola using long-term observations of colony demographics. We censused colonies, recording the number of juveniles, large females, and egg sacs, approximately every two months for two years. We also recorded the substrates supporting colony webs, including plant species and size, and the azimuth the colony occupied on the plant. Colonies in all regions showed cyclical patterns of growth and decline; however, regions were not synchronized, and seasonal effects differed between years. Colonies with fewer individuals at the initial observation were less likely to survive over the course of observations, and extinction rates were also influenced by an interaction between region and plant substrate. Small colonies were more likely to be extinct by the next census, but if they survived, they were more likely to have high growth rates compared to larger colonies. Despite the potential for high growth rates, high extinction rates depressed the average fitness of small colonies so that population growth rates peaked at intermediate colony sizes. Variance in egg sac production also peaked at intermediate colony sizes, suggesting that competitive interactions may increase the uneven distribution of resources in larger groups. Even if average fitness is high, if spiders can anticipate poor outcomes in large colonies, they may disperse to live solitarily or in smaller, less competitive groups.